The Influence of Technical Skills, Internship Opportunities and Institutional Support on The Readiness of Students of Polytechnic Malaysia Tuanku Syed Sirajuddin to Work in The Renewable Energy Sector - Sebayang, Saimara A M; Sari, Maya Macia; Faried, Annisa Ilmi; Binti Harun, Nor Harlinda; Ulzannah, Nisa (CV Raskha Media Group, 2025)
This study is design to analyze the influence of technical skills, internship opportunities, and institutional support on the readiness of students of Polytechnic Malaysia Tuanku Syed Sirajuddin to work, especially in the renewable energy sector. Due to the growing demand for skilled lobour in renewable energy,higher education institutitions are required to equip student with strong technical competencies,adequate internship exposure,and sufficient institutional support.The study plants to distribute 140 quetionaires to students from rewable -energy related program.. Data will be analiyzed using SPSS through descriptive analysis,validity testing,reliability testing,and regressionprocedures once collection is completed.The expected findings will highlight the significan role of technical skills,internship opportunities,and institutional support in strengthening student readniness for renewable energy workforce.